Complex systems and systems of systems engineering - Luzeaux, Dominique; Ruault, Jean-Rene; Wippler, Jean-Luc (ISTE ; Wiley, 2011)
With the growing maturity of information and communication technologies, systems have been interconnected within growing networks, yielding new services through a combination of the system functionalities. This leads to an increasing complexity that has to be managed in order to take advantage of these system integrations. This book provides key answers as to how such systems of systems can be engineered and how their complexity can be mastered. After reviewing some definitions on systems of systems engineering, the book focuses on concrete applications and offers a survey of the activities and techniques that allow engineering of complex systems and systems of systems. Case studies, ranging from emergency situations such as Hurricane Katrina and its crisis management or a generic scenario of a major traffic accident and its emergency response, to the establishment of a scientific basis in the Antarctic region illustrate key factors of success and traps to avoid in order to cope with such situations.